Complement system in cutaneous squamous cell carcinoma - Riihilä, Pilvi (Annales Universitatis Turkuensis D 1167, 2015)
Cutaneous squamous cell carcinoma (cSCC) consists 20% of keratinocytederived non-melanoma skin cancers (NMSC), the incidence of which is increasing globally. cSCC is the most common metastatic skin cancer and it causes approximately 20% of skin cancer-related deaths. At present, there are no molecular markers for predicting which cSCC lesions are aggressive or metastasize rapidly. UV radiation is the most important risk factor for cSCC. During the development of cSCC, normal epidermal keratinocytes are transformed and form actinic keratosis (AK), which progresses to cSCC in situ (cSCCIS, Bowen’s disease) and finally to invasive and metastatic cSCC. Inflammatory factors and cells are a part of cancer microenvironment and cSCC can develop in the chronically irritated skin or in the context of chronic inflammation. The complement system is a central part of innate immunity and it regulates normal immunological and inflammatory processes. In this study, the role of complement system components and inhibitors were studied in the progression of cSCC in culture and in vivo. Elevated expression of complement factor H (CFH), complement factor I (CFI), complement component C3 and complement factor B (CFB) was noted in cSCC cells in culture. The analysis with immunohistochemistry (IHC) revealed that the expression of CFH, CFI, C3 and CFB was specifically noted in tumor cells in vivo. The staining intensity of CFH, CFI, C3 and CFB was also stronger in invasive cSCC than in AK or cSCCIS samples. The knockdown of CFH, CFI and CFB with specific siRNAs decreased cSCC cell viability and migration, whereas the knockdown of C3 reduced only cSCC cell migration. Moreover, the knockdown of CFI, C3 and CFB inhibited growth of cSCC xenograft tumors established in SCID mice in vivo. In these tumors, CFI, C3 and CFB knockdown decreased the number of proliferating cells. Moreover, the knockdown of CFI increased local inflammation and complement activation. This study provides evidence for the roles of CFH, CFI, C3 and CFB in the tumor progression indicating these as molecular biomarkers and putative therapeutic targets of cSCC.

Komplementtijärjestelmä ihon okasolusyövässä Keratinosyyttiperäiset ei-melanoottiset syövät lisääntyvät maailmanlaajuisesti ja näistä syövistä 20% on ihon okasolusyöpää. Ihon okasolusyöpä on yleisimmin metastasoiva ihosyöpä ja se aiheuttaa 20% ihosyöpäkuolemista. Tällä hetkellä ihon okasolusyövän aggressiivisuutta tai nopeaa metastasointia ennustavia merkkitekijöitä ei tunneta. UV-säteily on tärkein riskitekijä ihon okasolusyövän kehittymiselle. Normaalit ihon keratinosyytit voivat muuttua ja muodostaa aktiinisia keratooseja, mitkä etenevät in situ muotoiseksi okasolusyöväksi (Bowenin tauti) ja lopulta ihon okasolusyöväksi. Tulehdussolut ja –tekijät kuuluvat syöpien mikroympäristöön. Myös ihon okasolusyöpä voi kehittyä kroonisesti ärsyyntyneelle tai tulehtuneelle ihoalueelle. Komplementtijärjestelmä on tärkeä osa ihmisen synnynnäistä immuniteettia ja se säätelee tulehduksellisia tapahtumasarjoja. Tässä työssä tutkittiin komplementtijärjestelmän komponenttien ja inhibiittoreiden osuutta ihon okasolusyövän kehittymisessä soluviljelmässä ja in vivo. Komplementin tekijä H:ta (CFH), komplementin tekijä I:tä (CFI), komplementin komponenttia C3:a ja komplementin tekjä B:tä (CFB) havaittiin kohonneina pitoisuuksina soluviljelmässä ihon okasolusyöpäsoluissa. Immunohistokemiallisessa analyysissä paljastui, että erityisesti kasvainsolut ilmensivät CFH:ta, CFI:tä, C3:a ja CFB:tä in vivo ja värjäysintensiteetti oli vahvempi okasolusyöpäsoluissa kuin aktiinisessa keratoosissa tai Bowenin taudissa. Kun spesifistä siRNA:ta käytettiin hiljentämään CFH:n, CFI:n ja CFB:n ilmaantuvuus, solujen elinkykyisyys ja liikkuminen väheni. C3 geenin hiljentäminen vähensi solujen liikkumista. Lisäksi CFI-, C3- ja CFB-geenin hiljentäminen vähensi okasolusyövän kasvua in vivo SCID-hiirissä kasvatetuissa ksenograftikasvaimissa. CFI-, C3- ja CFB-geenin hiljentäminen vähensi solujen jakautumista. CFI-geenin hiljentäminen lisäsi lisäksi paikallista tulehdusta ja komplementin aktivaatiota näissä kasvaimissa. Tässä tutkimuksessa osoitetaan CFH:n, CFI:n, C3:n ja CFB:n rooli okasolusyöpäkasvaimen kehittymisessä. CFH, CFI, C3 tai CFB voisivat myös toimia merkkitekijöinä ja hoitokohteina ihon okasolusyövälle.